Export structures, income inequality and urban-rural divide in China. (February 2020) - Zhu, Shengjun; Yu, Changda; He, Canfei
Abstract: Recent literature has linked export upgrading to income inequality, and found that regions exporting more sophisticated products tend to have lower levels of income inequality. Here, we extend the literature by stressing that regional income inequality is shaped not only by export product structure but also by export destination structure. We further scale down our analysis to the intra-regional level, and examine urban-rural inequality within a region. Few have related urban-rural inequality to export upgrading and a region's export product/destination structures. Hence, we contribute to the current literature by examining how regional export product/destination structures have shaped income inequality in general and urban-rural inequality in particular. Based on China's export data and income survey data, we show that export upgrading only contributes to the reduction of income inequality in China's urban areas. Urban-rural inequality tends to be more severe in regions that have more complex export product/destination structures, due to the concentration of export activities in urban areas and to some barriers that inhibits the flow of input factors (e.g. capital and labor) between rural and urban areas. Highlights: Regional income inequality is shaped by export product structure. Regional income inequality is shaped by export destination structure. Urban-rural inequality is shaped by export product structure. Urban-rural inequality is shaped by export destination structure.